2013
DOI: 10.1371/journal.pone.0082237
|View full text |Cite
|
Sign up to set email alerts
|

Bright Fluorescence Monitoring System Utilizing Zoanthus sp. Green Fluorescent Protein (ZsGreen) for Human G-Protein-Coupled Receptor Signaling in Microbial Yeast Cells

Abstract: G-protein-coupled receptors (GPCRs) are currently the most important pharmaceutical targets for drug discovery because they regulate a wide variety of physiological processes. Consequently, simple and convenient detection systems for ligands that regulate the function of GPCR have attracted attention as powerful tools for new drug development. We previously developed a yeast-based fluorescence reporter ligand detection system using flow cytometry. However, using this conventional detection system, fluorescence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
71
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 34 publications
(77 citation statements)
references
References 61 publications
4
71
0
2
Order By: Relevance
“…were used, unexpectedly resulting in a relatively similar codon usage to that in yeast (CAIs = 0.69~0.70 and GC contents = 44.9~45.0%) (Table 4). These support our previous result that ZsGreen (original codons) exhibited more intense fluorescence than EGFP (non-codon-optimized) when used as a fluorescent reporter protein34. Among the codon-optimized GFPs tested in this study, monomeric ymUkG1 and tetrameric yZsGreen exhibited the most intense green fluorescence in S. cerevisiae (Fig.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…were used, unexpectedly resulting in a relatively similar codon usage to that in yeast (CAIs = 0.69~0.70 and GC contents = 44.9~45.0%) (Table 4). These support our previous result that ZsGreen (original codons) exhibited more intense fluorescence than EGFP (non-codon-optimized) when used as a fluorescent reporter protein34. Among the codon-optimized GFPs tested in this study, monomeric ymUkG1 and tetrameric yZsGreen exhibited the most intense green fluorescence in S. cerevisiae (Fig.…”
Section: Resultssupporting
confidence: 91%
“…The plasmids used for the expression of the tested GFPs were constructed as follows: DNA fragments encoding the GFPs AcGFP1, TagGFP2 and mUkG1 were PCR-amplified from pAcGFP1 (Clontech Laboratories/Takara Bio, Shiga, Japan), pTagGFP2-tubulin (Evrogen, Moscow, Russia) and pmUkG1-S1 (Medical & Biological Laboratories, Nagoya, Japan) using primer pairs 1 and 2, 3 and 4, and 5 and 6; the fragments were then digested with SalI + BamHI and inserted into the same sites between the PGK1 promoter ( P PGK1 ) and the PGK1 terminator ( T PGK1 ) on pGK41633, yielding the plasmids pGK416-AcGFP1, pGK416-TagGFP2 and pGK416-mUkG1. For EGFP and ZsGreen, the previously constructed plasmids pGK416-EGFP33 and pGK416-ZsGreen34 were used. The expression plasmids used for codon-optimized GFPs (yEGFP, yAcGFP1, yTagGFP2, ymUkG1, yZsGreen, ymWasabi and ymNeonGreen) were constructed as follows: DNA fragments encoding the codon-optimized GFPs were PCR-amplified from the GeneArt ® Strings ™ DNA fragments using primer pairs 7 and 8, 9 and 10, 11 and 12, 13 and 14, 15 and 16, 17 and 18, and 19 and 20; the fragments were then digested with SalI + BamHI and inserted into the same sites between the P PGK1 and the T PGK1 on pGK41633, yielding the plasmids pGK416-yEGFP, pGK416-yAcGFP1, pGK416-yTagGFP2, pGK416-ymUkG1, pGK416-yZsGreen, pGK416-ymWasabi and pGK416-ymNeonGreen.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To provide a greater possibility to track antigens that might be degraded during hand-off or transit, we engineered another variant melanoma line, this time taking the parental B16 mela-noma cell line and introducing the bright and highly stable fluoro-phore ZsGreen (Nakamura et al, 2013), which is documented to resist both low pH and lysosomal degradation (Katayama et al, 2008), and which we have confirmed to be significantly less subject to degradation when ingested by phagocytes (data not shown). When we introduced these tumors into mice and removed dLN to analyze the myeloid populations, similarly to the previous assays we found that the fluorophore was again compartmentalized within CD103 + DC (Figure 3A).…”
Section: Resultsmentioning
confidence: 99%